Designing a Projectional Editor for Live Coding Using Design Thinking to Improve Teaching - Hosseinkord, Maryam (My University, 2021)
How can observation of a legacy system be used for design? To answer this question, we observed a teacher doing live coding with a conventional code editor and used the observations to design an editor better suited to this style of teaching. In particular, we found strong evidence that a projectional editor would better meet this need. Reflecting on this experience, we describe two types of requirements which can be inferred from observing a user using a legacy system: hidden requirements, in which users use existing features in unexpected ways, and novel requirements inferred from pain points observed in current system use.
Keywords: Projectional Editors; Code Editors; Design Thinking